Understanding the relational aspects of learning with, from, and about the other - Hovey, Richard (Nursing philosophy, 2011)
Frequently heard among healthcare providers, administrators, students, and educators, especially within the context of interprofessional collaboration, is the phrase: learning with, from, and about the other. Our purpose in writing this article was to explore the relational aspects of interprofessional collaboration and provide a conversational perspective on how this phrase may be co-constructed by members of the interprofessional team, to achieve a contextual understanding for enhanced practice. It is through understanding and analysing the meaning of commonly held words and phrases that we can begin to understand the differences between transactional ways of gaining knowledge and begin to understand how a transformational shift in attitude, identity, and practice can promote learning with, from, and about the other.